Heralded Generation of Two-photon NOON States for Precision Quantum Metrology - Smith, B; Mosley, P; Lundeen, J; Walmsley, I; IEEE (2008)
We experimentally demonstrate a heralded source of high-purity two-photon NOON states derived from heralded single-photon sources. © 2008 Optical Society of America.